An Analysis of Religious Tolerances as Found from Instagram Comment Section - Sugesti Pratiwi; Nia Maesaroh; Rika Uswatun Hasanah; Erika Indriyani (2022)
In the era of society 5.0 where everything can be digitized, social media is one of the important things in human life. Through social media, humans can do communication, sharing experiences, express their feeling, and showing an act about certain thing. Social media is a place to express and share all scopes of life, including religious tolerance. Religious tolerance can be found in human interactions on social media, seen from comments and engagements in social media’s post about an issue related to religion. By the research that will be conducted by the social media interactions, especially on instagram. Research formulation would be: How does Instagram promote the value of religious tolerance in Indonesia and how does it affect social interaction virtually?. This research aims to analyse value of religious tolerance in Indonesia and comment section in Instagram. This study used content Instagram and comment section to analyze value of religious tolerance in Indonesia and affect social interaction virtually.